Identifying the proton donor in electrocatalytic hydrogen evolution by a model hydrogenase - Riley E. Stein; Ashlee E. Wertz; Peter J. Moore; Hannah S. Shafaat (JBIC Journal of Biological Inorganic Chemistry, 2026)
Proton transfer is essential in all multi-electron transformations. Identifying the proton donor in such processes is crucial to understanding the catalytic mechanism and optimizing activity through pK a matching, which can enhance proton transfer rates. However, aqueous solutions offer multiple proton sources, which confounds clear identification of the catalytically relevant proton donor. In this work, we utilize a model hydrogenase, nickel-substituted rubredoxin (NiRd), which is capable of electrocatalytic hydrogen evolution. Prior mechanistic studies suggested a proton transfer process was involved in the rate determining step on the basis of isotopic substitution and kinetic modeling. In this study, the identity of the proton donor in this rate-determining step was investigated by employing a range of buffers with varied pK a values. The impacts of concentration and pH on catalytic currents and turnover frequencies (TOF) were investigated. These results suggest that intermolecular, buffer-dependent proton transfer is not the rate-determining step for catalysis under typical electrocatalytic conditions. Quantitative electrochemical simulations incorporating buffer information allowed extraction of intrinsic thermodynamic and kinetic parameters for catalysis. Ultimately, mechanistic distinctions between the NiRd system and other hydrogen-evolving catalysts suggest that controlling the proton donor may serve as a handle for modulating activity in an intentional manner.